Maternal Employment and Childhood Obesity in China: Evidence from the China Health and Nutrition Survey - Peng Nie; Alfonso Sousa-Poza (Institute for the Study of Labor (IZA), 2014)
Using five waves from the China Health and Nutrition Survey (CHNS), we investigate the association between maternal employment and obesity in children aged 3–17 in both rural and urban China. Using BMI and waist circumference as measures for pediatric adiposity, we provide scant evidence for its relation to maternal employment. We also find no strong association between maternal employment and our measures for children's diet and physical activity. Our study also suggests that grandparenting could have beneficial effects on childhood obesity.
Keywords: I12; J13; J22; 330; childhood obesity; maternal employment; China